Comparison of Cooperative Listening Team and Numbered Head Together Types of Learning Outcomes of Geography in the Material of Earth's Rotation and Revolution - Indri Yuniar Rachmawati; Ha Van Thang; Mike Marcell Zwick (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This study aims to determine differences in geography learning outcomes using cooperative learning models of listening team types, numbered heads together (NHT) and discussions. Methodology: This study used a Quasi-Experimental research method